Factors of Blockchain Adoption for FinTech Sector: An Interpretive Structural Modelling Approach - Gupta, Somya; Prasad Sahu, Ganesh (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2023)
Blockchain Technology (BT) is rapidly becoming one of the most promising emerging economy innovations. Financial Technology (FinTech) has been disrupted by blockchain, and its market size is growing by the day. Payments are closely related to banking, and blockchain has become very famous in the banking industry. This study aims to analyse the factors influencing behavioural intention to adopt blockchain in FinTech. Total 13 factors were extracted from the literature, and later relations among these variables were analysed using Interpretive Structural Modelling (ISM). The study's conceptual model was built and validated by academic experts working in blockchain. Later, MICMAC analysis was performed to study these variables' driving and dependence power. Blockchain has various challenges as well as opportunities but due to its advantages its implementation is recommended for FinTech. As per our results, the implementation of blockchain in FinTech is required as it promotes data privacy and traceability and involves more trust than traditional means.